ANALISIS SENYAWA FITOKIMIA DAUN Moringa oleifera DARI KAWASAN GEOTERMAL ACEH BESAR SEBAGAI KANDIDAT ANTIINFLAMASI - Santi, Tahara Dilla; Candra, Aditya (Poltekkes Kemenkes Bandung, 2024)
Indonesia is home to a diversity of herbal plants, particularly in Aceh. Moringa oleifera is traditional medicinal plant utilized by locals in the geothermal area Aceh Besar, recognized for its anti-inflammatory properties. However, the bioactive compounds in M. oleifera leaves sourced from Ie Seum have not been documented, making it challenging to explain the roles of the compounds scientifically to anti-inflammatory factors. This research aimed to identify the phytochemical compounds in the ethanol extract of M. oleifera leaves (referred to as EDM) and analyze the physicochemical characteristics of the soil in the geothermal area. This study used a qualitative design to identify EDM compounds with GC-MS and soil physicochemistry. The identification of EDM compounds is conducted through gas chromatography with mass spectrometry (GC-MS). The physicochemical properties of the soil are assessed by examining its texture, pH, organic carbon content, total nitrogen, exchangeable cations, and phosphorus. Sample collection on topsoil (0-20 cm) with an area of ​​100cmx100cm on one land where M. oleifera plants grow in Ie Seum area in September 2024. A soil sample of 500g was using several methods, namely the hydrometermethod, pH meter, Walkey and Black, ammonium acetate 1M pH 7, Kjeldahl, KCl 1N, Bray 1, HCl 25%, and DTPA extraction. The soil test result showed classified as silty clay. The results GC-MS indicated the presence 11 metabolites, including linolenic acid, phytol, 9,12,15-octadecatrienoic acid ethyl ester, hexadecanoic acid, neophytadiene, gamma-tocopherol, vitamin E, squalene, icosane, and beta-pinene. EDM from the Ie Seum contains compounds that are beneficial in anti-inflammatory.